2021
DOI: 10.1123/ssj.2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

Jiu-Jitsu and Society: Male Mental Health on the Mats

Abstract: The growth in mixed martial arts (MMA) gyms worldwide, along with adjunct media discourse has been matched by the number of participants, characterized by the dedication and sacrifice imbued. These factors catalyzed this research which sought initially to understand the motivations of MMA gym members and the role that the training plays in their lives. Through an immersive participant ethnography lasting 3 years, the author trained, socialized, fought, and competed with members of an urban MMA gym in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In sociological literature, several scholars have engaged in MA practice to understand it further. Drawing on a three-year ethnography, Sugden (2021) trained and competed in MA and found that it had great implications for mental health. Specifically, Sugden (2021) highlighted how students needed to endure training to acquire new techniques, test them, and engage in a trial-and-error process, which is heavily time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In sociological literature, several scholars have engaged in MA practice to understand it further. Drawing on a three-year ethnography, Sugden (2021) trained and competed in MA and found that it had great implications for mental health. Specifically, Sugden (2021) highlighted how students needed to endure training to acquire new techniques, test them, and engage in a trial-and-error process, which is heavily time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on a three-year ethnography, Sugden (2021) trained and competed in MA and found that it had great implications for mental health. Specifically, Sugden (2021) highlighted how students needed to endure training to acquire new techniques, test them, and engage in a trial-and-error process, which is heavily time-consuming. In addition, facing several setbacks as a novel student (e.g., losing to lesser opponents), MA entails developing resilience and self-regulation not only in the immediate situational context.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations